Korelasi antara jenis pakan komersial dengan jenis kristal pada kasus kucing flutd (feline lower urinary tract disease) di rumah sakit hewan dinas peternakan Jawa Timur - Ratna Widyawati; Bagus Uda Palgunadi; Lailia Dwi Kusuma Wardhani; Dini Fadhilla Samjaya (VITEK : Bidang Kedokteran Hewan, 2022)
Feline lower urinary tract disease (FLUTD) is a term used to describe various causes of lower urinary tract disorders in cats which include idiopathic, urolithiasis, urinary tract infections, anatomical and neurological disorders. Use of commercial feed is one of the causes of Flutd formation. This study was to determine the correlation between commercial feed types and crystal types in the case of FLUTD cats at the Animal Hospital of East Java Province. The sample is primary data obtained directly by collection of fresh urine and through interviews with animal owners. As many as 30 fresh urine samples were sedimented and then observed under a microscope. The results of observations of urine sedimentation with a microscope showed that 16 cats had crystals in their urine. The highest percentage of struvite crystals was 12 cats (40%). Meanwhile, in 14 cats (46.7%) no crystals were found in the urine. It is known that the sensitivity of the urine sedimentation test is 64% and the specificity is 97%. There are different types of crystals in commercial feed with the same brand. the same brand of commercial feed can produce different types of crystals. This is due to many other factors that trigger the formation of crystallization. The urine sedimentation test is very accurate to detect cases of FLUTD and crystals in the urine